Unity Food Hub: Creating New Opportunities for Local Farms - Gold, Michael (Maine Policy Review, 2011)
Unity, Maine, as described in this case study, has grown into a “food hub,” as defined by the USDA. With support from the Maine Farmland Trust, a number of local development options are being explored.
Keywords: Maine; food hub; local foods